A review in the primary nanophases in titanium alloys: Formation, evolution and their effects on mechanical properties - Leying Chen; Yahong Ding; Ruyi Ji; Run Li; Shaoyang Wang; Haicheng Zhang; Hengjun Luo; Jian Mao (Journal of Materials Research and Technology)
Titanium alloys are typically processed using various heat treatment or thermomechanical processing to precipitate different nanoscale phases within the matrix through distinct formation mechanisms. During the processing, the association among the processing parameters, formation mechanisms, and types of nanophases is closely related, and the effects of different nanophases on the mechanical properties of titanium alloys vary significantly. Consequently, investigating the processing methods, formation mechanisms, and their relationship with mechanical properties concerning the precipitation of different nanophases in titanium alloys is of paramount importance. Currently, there are relatively few relevant reviews. This article discusses the main formation mechanisms of four nanophases including α phase, α′ phase, α″ phase, and ω phase in the processing of dual-phase titanium alloys, metastable β titanium alloys, and β titanium alloys. It summarizes how the size and number of these nanophases affect the mechanical properties, along with the distinct strengthening mechanisms and their effects on titanium alloys associated with these four nanophases. Furthermore, this review discusses that when nanoscale α′ phase forms in the titanium alloy matrix, the strength of alloys can reach 1200–1600 MPa, while maintaining a good elongation range (9–22%). These findings provide insights for designing high-strength-ductility titanium alloys and are potentially applicable to other titanium alloys.